One pot synthesis of Cu–Ni–S@Ni foam for the simultaneous removal and detection of norfloxacin. (1st January 2023) - Jiang, Xincheng; An, Yanyan; Huang, Yaoyao; Ding, Wei; Sun, Manli; Li, Hong; Zheng, Huaili
Abstract: The residual antibiotics in the environment will pose a threat to the environment and human health. Thus, it is imperative to develop a smart water treatment material to remove and detect antibiotics from aqueous environment simultaneously. In this study, magnetic Cu–Ni–S@Ni foam was synthesized by liquid phase vulcanization method to in-situ load Cu–Ni–S nanostructures on the surface of Ni foam. The novelty of this material is the combination of adsorption-flocculation technology and semi-quantitative detection technology. Batch experiments showed that Cu–Ni–S@Ni foam has a high removal rate of norfloxacin (NOR) (96.92%), wide pH adaptability (pH = 4.0–10.0) and strong ion interference resistance (0.1–100 mmol/L). According to the Langmuir isotherm, the removal capacity can reach 417.4 mg/g at 25 °C, which is much higher than that of other water treatment agents reported in most studies. Characterization analysis indicated that the main removal mechanisms are surface complexation, cation bridging, electrostatic attraction, precipitation and flocculation. Transmission FTIR detection experiments showed that NOR on Cu–Ni–S@Ni foam has easily recognizable FTIR fingerprints; the intensity of characteristic peaks roughly reflects the concentration information of NOR to some extent. This semi-quantitative detection method, requiring simple operation without the fabrication of KBr tablet, has a wide linear range (5–100 mg/L) and a low limit of detection (4.6 mg/L). Therefore, Cu–Ni–S@Ni foam can be used for simultaneous removal and semi-quantitative detection of NOR in wastewater. It has potential application value in wastewater treatment and water quality monitoring. Graphical abstract: Image 1 Highlights: The one pot synthesized Cu–Ni–S@Ni foam could remove and detect NOR simultaneously. Both adsorption and flocculation, induced by ligand-promoted dissolution, were involved in the removal process. The Cu–Ni–S@Ni foam performed high removal capacity (417.4 mg/g at 25 °C) for NOR. A semi-quantitative detection method based on transmission FTIR was developed without the fabrication of KBr tablet.